Salinity Stress in Wheat (Triticum aestivum L.) in the Changing Climate: Adaptation and Management Strategies - EL Sabagh, Ayman; Islam, Mohammad Sohidul; Skalicky, Milan; Ali Raza, Muhammad; Singh, Kulvir; Anwar Hossain, Mohammad; Hossain, Akbar; Mahboob, Wajid; Iqbal, Muhammad Aamir; Ratnasekera, Disna; Singhal, Rajesh Kumar; Ahmed, Sharif; et al. (Frontiers in Agronomy, 2021)
Wheat constitutes pivotal position for ensuring food and nutritional security; however, rapidly rising soil and water salinity pose a serious threat to its production globally. Salinity stress negatively affects the growth and development of wheat leading to diminished grain yield and quality. Wheat plants utilize a range of physiological biochemical and molecular mechanisms to adapt under salinity stress at the cell, tissue as well as whole plant levels to optimize the growth, and yield by off-setting the adverse effects of saline environment. Recently, various adaptation and management strategies have been developed to reduce the deleterious effects of salinity stress to maximize the production and nutritional quality of wheat. This review emphasizes and synthesizes the deleterious effects of salinity stress on wheat yield and quality along with highlighting the adaptation and mitigation strategies for sustainable wheat production to ensure food security of skyrocketing population under changing climate.